Healthcare Utilization, Induced Labour and Caesarean Section in the Pregnancy after Stillbirth: A Prospective Study - Hina, Urooj; Baqai, Shehla; Choudry, Abeera; Saeed, Saira; Urooj, Uzma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To measure the healthcare utilization, induced labour and frequency of C-sections in the pregnancy after stillbirth in the tertiary care setting.Study Design: Comparative prospective study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018-Sep 2019.Methodology: A total of 181 pregnant women were recruited and divided into two groups; Group-1=75pregnant women afterstillbirth and Group-2=106 pregnant women after live birth. Data regarding the healthcare utilization, induced labour, onset and mode of delivery and caesarean section was collected after the informed consent.Results: Mean age of the study population (n=181) was 28.73±5.0 years (Range:19-40 years). Group-1 females had more antenatal visits (7.88±3.60) compared to women of Group-2 (6.18±2.90) (p-value=0.001). History of Induced labour and caesarean section were also more in Group-1 (Stillbirth-Group). Pregnant women in Group-1 were found to be significantly more worried about the pregnancy outcome in 53(70.7%) as compared to Group-2 in 5(4.7%) with a p-value of